THU0247 The Effect of Hydroxychloroquine and IRAK4 Inhibition on The IFN-A and TNF-A Production Induced by Sle Related Immune Complexes. (15th July 2016) - Hjorton, K.; Hagberg, N.; Berggren, O.; Mo, J.; Sandling, J.; Eloranta, M.-L.; Rönnblom, L.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) have an ongoing interferon (IFN)-α production due to the stimulation of Toll-like receptors (TLR) 7 and 9 in plasmacytoid dendritic cells (pDCs) by immune complexes (ICs) containing self-derived nucleic acid. Such interferogenic ICs also trigger the production of TNF-α by several immune cells. Produced TNF-α in SLE contributes to organ inflammation such as nephritis and arthritis, but can also modulate the central autoimmune process as demonstrated by the induction of a lupus-like syndrome after anti- TNF-α treatment. Objectives: To clarify the effect on IFN-α and TNF-α production by IC-stimulated immune cells from healthy individuals and SLE patients exposed to hydroxychloroquine (HCQ) and an IRAK4 inhibitor Methods: pDC and NK cells were isolated from peripheral blood of healthy individuals and monocyte depleted PBMCs from SLE patients. Cells were stimulated with RNA-containing ICs (RNA-IC) comprised of SLE-IgG and U1snRNP particles in the presence or absence of HCQ, which blocks endosomal TLR7/9 activation, or a IL-1 receptor associated kinase (IRAK) 4 inhibitor (AZ13732754–004) acting downstream of TLR 7/9. IFN-α and TNF-α production was measured after 20 h by immunoassays or by intracellular staining using flow cytometry. Results: RNA-IC induced IFN-α production selectively in pDC, whereas TNF-α was produced by both pDC and NK cells. Co-cultivation of pDC and NK cells enhanced the production of IFN-α (28-fold) and TNF-α (15-fold). TNF-α was rapidly produced by NK cells (5 h), but exhibited a delayed production in pDC (9 h). All IFN-α positive pDCs (13.6%) were TNF-α positive, whereas a fraction of pDCs (7.1%) were only TNF-α positive. HCQ completely inhibited the IFN-α and TNF-α production by pDCs, but did not affect TNF-α production by NK cells. Preliminary studies showed that cells from HCQ-treated SLE patients produced little IFN-α (mean 3 U/ml vs 27 U/ml in not HCQ-treated) in response to RNA-IC [NH1], whereas TNF-α production was maintained (mean 760 U/ml [NH2] vs 407 U/ml in not HCQ-treated). Inhibition of IRAK4 effectively blocked IFN-α production in both pDC (94%) and pDC-NK cell co-cultures (91%). Conclusions: The IFN-α production induced by RNA-IC is completely blocked by HCQ and the IRAK4 inhibitor AZ13732754–004, suggesting that administration of an IRAK4 inhibitor could be an effective treatment strategy in SLE. The observation that HCQ inhibited the pDC derived TNF-α production, but not TNF-α released from other immune cells in SLE patients, may explain why HCQ treatment is only partially effective in SLE. In addition, our observation indicates that RNA-IC stimulated TNF-α production is induced by different mechanisms in pDC and NK cells. Further investigations are needed to clarify if IRAK4 inhibition has a broader inhibitory effect than HCQ on the production of proinflammatory cytokines, and if inhibition of IRAK4 should be explored as a therapeutic option in SLE. Disclosure of Interest: K. Hjorton Grant/research support from: Study partly financed by Astra Zeneca, N. Hagberg: None declared, O. Berggren: None declared, J. Mo: None declared, J. Sandling: None declared, M.-L. Eloranta: None declared, L. Rönnblom: None declared